EFFECTS OF SYNTHETIC DISEASE-MODIFYING ANTIRHEUMATIC DRUGS, BIOLOGICAL AGENTS, AND PSYCHOPHARMACOTHERAPY ON THE MENTAL DISORDERS IN PATIENTS WITH RHEUMATOID ARTHRITIS - A. A. Abramkin; T. A. Lisitsyna; D. Yu. Veltishchev; O. F. Seravina; O. B. Kovalevskaya; E. L. Nasonov (Научно-практическая ревматология)
Mental disorders (MDs) of the anxiety-depressive spectrum (ADS) and cognitive impairment (CI) are characteristic of the majority of patients with rheumatoid arthritis (RA); however, the effects of disease-modifying antirheumatic drugs (DMARDs), biological agents (BAs), and their combinations with psychopharmacological drugs (PPDs) on these abnormalities have been insufficiently studied. Objective: to investigate trends in the incidence of MDs in RA patients receiving different treatment regimens.Subjects and methods. The investigation included 128 RA patients (13% men and 87% women) who fulfilled the 1987 American College of Rheumatology criteria; their mean age was 47.4±0.9 years; the median duration of RA was 96 [48; 228] months. RA activity was found to be high, moderate, and low in 48, 56, and 24 patients, respectively. DAS28 averaged 5.34±0.17. 80% of the patients received DMARDs. MDs were diagnosed based on ICD-10 coding, by using a semi-structured interview and scales, such as the Hospital Anxiety and Depression Scale, the Hamilton Anxiety Scale, and the Montgomery-Asberg Depression Rating Scale. Clinical and psychological procedures were used to diagnose CI. At the study inclusion stage, ADS disorders were detected in 123 (96.1%) patients; CI was found in 88 (68.7%). Forty-one (32.1%) patients were diagnosed with major depression (an obvious or moderate depressive episode), 53 (41.4%) patients had minor depression (a mild depressive episode and dysthymia), and 29 (22.6%) had anxiety disorders (ADs) (adjustment disorders with anxiety symptoms, as well as generalized anxiety disorder). The dynamics of MDs was estimated in 112 (87.5%) of the 128 patients and in 83 (64.8%) at one- and five-year follow-ups, respectively. The following groups were identified according to the performed therapy: 1) synthetic DMARDs (n = 39); 2) synthetic DMARDs + PPDs (n = 43); 3) BAs + DMARDs (n = 32); 4) BAs + DMARDs + PPDs (n = 9).Results and discussion. In Group 1, the frequency of major depression increased insignificantly from 25% to 32.2 and 33.3% (p = 0.36) at one- and five-year follow-ups, respectively; that of minor depression decreased from 51% to 48.4 (p = 0.5) and 50% (p = 0.6) respectively; the number of patients with ADs declined significantly from 24% to 3.2 (p = 0.018) and 4.2% (p = 0.021), respectively. The frequency of CI rose from 63.5% to 64.5 and 81.8%, respectively (p = 0.12). In Group 2, the frequency of major depression decreased from 43 to 19% (p = 0.049) at one-year follow-up; and none of the patients was found to have ADS disorders at five-year follow-up (p < 0.001); the frequency of minor depression dropped from 38% to 23.8 and 7.1% at one-year (p = 0.35) and five-year (p = 0.002) follow-ups, respectively; the frequency of ADs fell from 19% to 4.8 (p = 0.044) and 0% (p = 0.012), respectively. The frequency of CI decreased insignificantly from 80.9% to 76.2 (p = 0.39) and 61.5% (p = 0.061), respectively. In Group 3 treated with BAs, the frequency of major depression increased statistically insignificantly from 31.2% to 37.9 (p = 0.39) and 42.8% (p = 0.28) at oneand five-year follow-ups, respectively; the frequency of minor depression rose insignificantly from 37.5% to 48.3 (p = 0.28) and 52.4% (p = 0.21), respectively; and that of ADs dropped from 25 to 0% at one-year (p = 0.003) and five-year (p = 0.011) follow-ups. Moreover, the frequency of CI increased from 75% up to 79.3 (p = 0.46) and 90% (p = 0.16) at one- and five-year follow-ups respectively. In Group 4, the frequency of major depression decreased significantly from 66.7 to 22.2% (p = 0.076) and complete regression (p = 0.004) at one- and five-year follow-ups, respectively; that of minor depression increased slightly from 11.1 to 33.3% (p = 0.28) due to the transformation of major depression into minor one at one- and five-year follow-ups, respectively; the frequency of ADs fell from 22.2% to zero at 5 years; and the incidence of CI declined 66.7 to 57.1% (p = 0.54).Conclusion. Synthetic DMARDs had no effect on the ADS disorders and CI in patients with RA; BAs promoted the regression of ADs and did not affect the progression of depression and CI. A combination of DMARDs and BAs used at the adequate dose of PPDs for the same period led to the regression of ADS disorders and the reduction in the frequency of CI.